Pelatihan K3 Laboratorium di Lingkungan Perguruan Tinggi: Upaya Preventif Kecelakaan Kerja di Masa Transisi Digital - Nadia Maharani; Nur Halimah; Desy Cahya Widianingrum; Susanti; Meireni Cahyowati; Harvey Febrianta (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Occupational Safety and Health (OSH) in laboratories is a fundamental aspect in supporting laboratory and research activities at universities, particularly in the field of animal science, which involves potential biological, chemical, and physical hazards. During the digital transition, the complexity of occupational risks has increased alongside the increasingly intensive use of laboratory technology. This community service activity aims to enhance the understanding and awareness of the academic community regarding the implementation of laboratory OSH as a preventive measure against workplace accidents. The methods employed include outreach, training, and the delivery of case-study-based materials online via the Zoom Meeting. A total of 151 participants took part in the activity, comprising students, faculty members, and laboratory staff from various universities. The results of the activity indicate that participants gained a comprehensive understanding of hazard identification, risk control strategies based on the 3E approach, the implementation of Good Laboratory Practice (GLP), and the importance of near-miss reporting. This training contributes to building a culture of workplace safety and enhancing preparedness for emergency situations in the laboratory.